Which Factor Is More Relevant to the Effectiveness of the Cognitive Intervention? A Meta-Analysis of Randomized Controlled Trials of Cognitive Training on Symptoms and Executive Function Behaviors of Children With Attention Deficit Hyperactivity Disorder - Chen, Shuxian; Yu, Jinglong; Zhang, Qiang; Zhang, Jin; Zhang, Ying; Wang, Junhong (Frontiers in Psychology, 2022)
Objective: Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by developmentally inappropriate inattention, hyperactivity, and impulsivity. Multiple cognitive training appeared to be more effective than working memory training, but the evidence remains insufficient, particularly for the subgroup symptoms and executive function behaviors at home. Further analysis of the impact of factors on the effectiveness would facilitate the development of cognitive training. Methods: We searched PubMed, Cochrane Library, Psyche, Embase, Chinese Biomedical Literature Database, CNKI, and Weifang Database, and included randomized controlled trials (RCTs) of children with ADHD undergoing cognitive intervention. Metaanalysis and univariate metaregression were performed by STATE. The risk of bias was assessed with the Cochrane risk of bias tool 2.0 by the two investigators separately. This study was registered with INPLASY, number INPLASY202140065. Results: We included 17 RCTs in the systematic review, with a combined 1,075 participants. For metaanalyses of both subgroups of ADHD symptoms and the executive function behaviors, the test of published bias failed to reach the p < 0.05 level. When all of the training are considered together, cognitive training can improve the presentation of inattention symptoms [SMD = −0.390, 95%CI (−0.675, −0.104)] and executive function behaviors (SMD = −0.319, 95%CI (−0.527, −0.111)]. In the subgroup analysis, the effects of working memory training on both presentations were not statistically significant. In contrast, the multiple cognitive training had significant effects on the presentation of inattention symptoms [SMD = −0.507, 95% CI (−0.722, −0.292)], hyperactivity/impulsivity [SMD = −0.305, 95% CI (−0.518, −0.09)], and the executive function behaviors [SMD = −0.499, 95%CI (−0.707, −0.290)]. In addition, metaregression analysis showed that only training frequency did significantly impact the symptoms of ADHD and the executive function behaviors. Conclusion: This study showed that improvements in symptoms and executive function behaviors were related to the domains of cognitive intervention. The findings suggest that multiple domains of cognitive training and moderate training frequency may have wider clinical benefits. All the above results highlight further research in refining the executive functions of children with ADHD and developing individually tailored cognitive intervention on homes based for children with vulnerable executive functions. Systematic Review Registration: [http://inplasy.com/], [INPLASY202140065].